Le Consulat général de France à Québec et à Montréal de 1859 à 1914 - Savard, Pierre (Presses de l'Université Laval, 1971)
Keywords: Consulat général de France

Ne faire qu'un seul peuple? Iroquois et Français à l'"âge héroïque" de la Nouvelle-France (1600-1660) - Beaulieu, Alain (Université Laval, 1992)
Keywords: Autochtones; Français; Iroquois

La Nouvelle-France sous Joseph-Antoine Le Febvre de La Barre, 1682-1685: lettres, mémoires, instructions et ordonnances - Dubé, Pauline (Septentrion, 1993)
Keywords: Autochtones; Français; Gouverneurs

Anciens Montréalais I: Bénigne Basset, notaire royal, 1639-1699 - Mclennan, William (Le Canada français, 1919)
issued: 1919/1920
Keywords: Basset; Bénigne; Notaires

La fin des alliances franco-indiennes: enquête sur un sauf-conduit de 1760 devenu un traité en 1990 - Vaugeois, Denis (Boréal, 1995)
Keywords: Autochtones; Français

Colonial Government Finances in New France, 1700-1750 - Desbarats, Catherine Macleod (Université McGill, 1993)
This thesis considers government finances in New France during the first half of the eighteenth century. By looking directly at government accounts from Canada and l'Ile Royale, and at the administrative structures which gave rise to them, it seeks to reconcile ostensibly rival quantitative and 'administrative' approaches to the literature on France's Ancien regime finances. Evidence is found to suggest that colonial finances emerged as an integral part of French naval finances, not as a result of deliberate policy, but as a by-product of the continued presence of naval troops in the colonies and of the early failure of the Domaine d'Occident to generate net revenue flows to France. Especially in the case of Canada, the accounts of the colonial branch of the naval treasury do not yield a continuous series of figures. Nonetheless, they provide ranges for the size, distribution and changes through time of government expenditure in the colonies, as well as indications of its importance relative to the general level of economic activity, and of the net cost to France of running its North American colonies.

Les relations franco-canadiennes de 1896-1911 - Prévost, Philippe (Université Paris-Sorbonne - Paris IV, 1984)
Keywords: Consulat général de France; Fabre (famille)

Un homme politique ultramontain: F.-X.-A. Trudel - Garon, Louis (Les ultramontains canadiens-français, 1985)
Keywords: Trudel; François-Xavier-Anselme; Ultramontains

La Grande Paix de Montréal de 1701: les voies de la diplomatie franco-amérindienne - Havard, Gilles (Recherches amérindiennes au Québec, 1992)
Keywords: Autochtones; Français; Grande Paix de Montréal

CASSIDY, FRANCIS - Sylvain, Philippe (Dictionnaire biographique du Canada, 1972)

CAMPBELL, FRANCIS WAYLAND - Milner, Elizabeth Hearn (Dictionnaire biographique du Canada, 1994)

HINCKS, sir FRANCIS - Ormsby, Wiliam (Dictionnaire biographique du Canada, 1982)

BADGLEY, FRANCIS (1767-1841) - Senior, Elinor Kyte (Dictionnaire biographique du Canada, 1988)

JOHNSON, sir FRANCIS GODSCHALL - White, Clinton O. (Dictionnaire biographique du Canada, 1990)

Le notaire en Nouvelle-France - Vachon, André (Université Laval, 1956)
Keywords: Notaires

Les drapeaux militaires en Nouvelle-France - Chartrand, René (Material History Review / Revue d’histoire de la culture matérielle, 1995)
Number: 1
Keywords: Armée

Milieu ouvrier canadien-français et délinquance juvénile - Bertrand, Francine (Université de Montréal, 1971)
Keywords: Délinquance; Enfants

Lemoyne d'Iberville: A Soldier of New France - Crouse, Nellis Maynard (The Ryerson Press/Cornell University Press, 1954)
Keywords: Le Moyne d'Iberville et d'Ardillières; Pierre

Les commissaires de la Marine en Nouvelle-France - Roy, P.-G. (Bulletin des recherches historiques, 1918)
Keywords: Commissaires de la Marine

Les huissiers de Montréal sous le régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1926)
Number: 2
Keywords: Huissiers

Les interprètes à Montréal sous le régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1928)
Number: 3
Keywords: Interprètes

Les pompiers de Montréal sous le régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1941)
Number: 6
Keywords: Pompiers

Les trottoirs à Montréal sous le régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1937)
Number: 10
Keywords: Rues

La juridiction royale de Montréal sous le régime français - Thibon, Geneviève (Université de Montréal, 1968)

Jean Talon et la colonisation de la Nouvelle-France - Lamontagne, Roland (Université de Montréal, 1953)

L’eau-de-vie en Nouvelle-France, 1629-1672 - Lamontagne, Roland (Université de Montréal, 1951)
Keywords: Alcool

Les juges de Montréal sous le régime français, 1648-1760 - Massicotte, E.-Z. (Les Cahiers des Dix, 1943)
Keywords: Juges

Les greffiers de Montréal sous le régime français, 1648-1760 - Massicotte, E.-Z. (Bulletin des recherches historiques, 1925)
Number: 4
Keywords: Greffiers

Les juges de Montréal sous le régime français - 1648-1760 - Massicotte, E.-Z. (Bulletin des recherches historiques, 1921)
Number: 6
Keywords: Juges

La conscription de 1917 d'après les journaux français de Montréal - Chantelois, René (Université de Montréal, 1967)
Keywords: Conscription

Philippe de Rigaud de Vaudreuil, Governor of New France 1703-1725 - Zoltvany, Yves F (McClelland and Stewart, 1974)
Keywords: Gouverneurs; Rigaud de Vaudreuil; Philippe de

De la Champagne à la Nouvelle-France, Claude de Ramesay (1659-1724) - Litalien, Raymonde (Catalogue de l'exposition Le Canada de Louis XIV, 1980)
Keywords: Gouverneurs; Ramezay; Claude de

Un défenseur de la Nouvelle-France, François Piquet, le "Canadien" (1708-1781) - Chagny, André (Librairie Emmanuel Vitte, 1913)
Keywords: Autochtones; Communautés religieuses; Missions; Piquet; François; Sulpiciens

Duels et coups d'épée à Montréal sous le Régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1915)
Keywords: Duel

Les procureurs fiscaux et royaux à Montréal sous le régime français - Massicotte, E.-Z. (Bulletin des recherches historiques, 1926)
Number: 7
Keywords: Avocats

L'exécuteur de la haute justice au Canada sous le régime français - Lachance, André (Université Laval, 1964)

L'invasion du Canada en 1775, d'après les historiens canadiens-français - Kelly, John E. (Université Laval, 1941)
Keywords: Américains; Armée; Historiens

Histoire et idéologie du groupe canadien-français du parti communiste, 1925-1945 - Fournier, Marcel (Université de Montréal, 1969)
Keywords: Communistes; Idéologies; Partis politiques

Histoire et idéologie du groupe canadien-français du parti communiste (1925-1945) - Fournier, Marcel (Socialisme 69, 1969)
Keywords: Communistes; Idéologies; Partis politiques

Les marguilliers de la paroisse Notre-Dame de Montréal en Nouvelle-France : étude prosopographique - Verdoni, Cécile (Université de Montréal et Université Lumière Lyon II, 1999)
Keywords: Marguilliers; Notre-Dame (paroisse)

Les couples en difficulté aux XVIIe et XVIIIe siècles: les demandes de séparation en Nouvelle-France - Savoie, Sylvie (Université de Sherbrooke, 1986)
Keywords: Mariage

Les tribunaux et les officiers de justice, à Montréal, sous le régime français, 1648-1760 - Massicotte, E.-Z. (Mémoires et comptes rendus de la Société royale du Canada, 1916)
Keywords: Juges; Tribunaux

Dollard Des Ormeaux and the Fight at Long Sault: Was Dollard the Saviour of New France? - Lanctot, Gustave (Canadian Historical Review, 1932)
Number: 2
Keywords: Autochtones; Dollard Des Ormeaux; Adam

La redoute de Dollard à la Baie des Sauvages. Un fort défendu par dix-sept Français - Barbeau, Marius (Revue canadienne de géographie, 1959)
issued: 1959-07/1959-12
Keywords: Autochtones; Dollard Des Ormeaux; Adam

Les officiers d'état-major des gouvernements de Québec, Montréal et Trois-Rivières sous le régime français - Roy, P.-G. (Revue canadienne, 1917)
Number: 5
Keywords: Armée

Justice et règlement des conflits dans le gouvernement: une étude de Montréal à la fin du Régime français - Garneau, Jean-Philippe (Université du Québec à Montréal, 1995)

De la Nouvelle-Angleterre à la Nouvelle-France: l'histoire des captifs anglo-américains au Canada entre 1675 et 1760 - Fournier, Marcel (Société généalogique canadienne-française, 1992)
Keywords: Américains; Captifs

Un aspect des relations sociales en Nouvelle-France: les voies de fait dans la juridiction de Montréal, 1700-1760 - Leclerc, Jean-François (Université de Montréal, 1985)
Keywords: Criminalité

«C'est l'eau-de-vie qui a commis ce meurtre». Alcool et criminalité amérindienne à Montréal sous le Régime français - Dickinson, John A. (Études canadiennes / Canadian Studies, 1993)
Number: 35
Keywords: Alcool; Autochtones; Criminalité

Two of the Early English-Speaking Bâtonniers of the Montreal Bar - Fabre-Surveyer, É. (Mémoires et comptes rendus de la Société royale du Canada, 1949)
Keywords: Avocats; Barreau; Cassidy; Francis; Kerr; W. H. H.

La Révolution française et les Rébellions de 1837 et 1838 dans le Bas-Canada - Grenon, Michel; Bernard, Jean-Paul (La Révolution française au Canada français, 1991)
Keywords: Rébellions

Henri Bourassa: une analyse de sa pensée - Drolet, Jean (Idéologies au Canada français 1900-1929, 1974)
Keywords: Bourassa; Henri; Idéologies

Henri Bourassa: The Catholic Social Order and Canada's Mission - Levitt, Joseph (Idéologies au Canada français 1900-1929, 1974)
Keywords: Bourassa; Henri; Idéologies

L'action politique ouvrière, 1899-1915 - Rouillard, Jacques (Idéologies au Canada français 1900-1929, 1974)
Keywords: Parti ouvrier; Partis politiques

Le Parti ouvrier-progressiste en crise, 1946-1956 - Comeau, Robert; Dionne, Bernard (Idéologies au Canada français 1940-1976, Tome III, 1981)
Keywords: Communistes; Parti ouvrier; Partis politiques

Le Parti communiste canadien au Québec pendant la seconde guerre mondiale, 1939-1945 - Comeau, Robert; Dionne, Bernard (Idéologies au Canada français 1940-1976, Tome III, 1981)
Keywords: Communistes; Partis politiques

Les poubelles du Québec : d'un enjeu de groupe de pression à un enjeu de mouvement social - Séguin, Michel; Maheu, Louis; Vaillancourt, Jean-Guy (Canadian Review of Sociology and Anthropology / Revue canadienne de sociologie et d'anthropologie, 1995)
Number: 2
Keywords: Groupes populaires